2015
DOI: 10.4103/1117-1936.170738
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and functional evaluation of peroneal nerve regeneration in rabbit following topical hyaluronic acid or tacrolimus application after nerve repair

Abstract: Electrophysiological analyses and functional evaluations based on the TSI indicate that HA and FK-506 exert similar, positive effects on nerve regeneration that are superior to those observed in response to saline treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Recently, we published two original articles that compare the effects of HA and FK-506 on nerve regeneration. We found that our electrophysiological and biomechanical measurements as well as our results of functional evaluations indirectly indicate that the effects of HA and FK506 on nerve regeneration are similar [98,99].…”
Section: Tacrolimusmentioning
confidence: 76%
See 2 more Smart Citations
“…Recently, we published two original articles that compare the effects of HA and FK-506 on nerve regeneration. We found that our electrophysiological and biomechanical measurements as well as our results of functional evaluations indirectly indicate that the effects of HA and FK506 on nerve regeneration are similar [98,99].…”
Section: Tacrolimusmentioning
confidence: 76%
“…According to our results, HA and FK506 appear to have similar effects (P > 0.05) with respect to preventing scar formation and improving nerve regeneration compared with saline (P < 0.05) [80,98]. However, it should be mentioned that we observed no significant differences in biomechanical properties in the HA and FK506 groups compared to the saline group (P > 0.05) [99].…”
Section: Mechanisms Of Action Referencesmentioning
confidence: 92%
See 1 more Smart Citation
“…Electrophysiological studies and functional evaluation (toe-spreading index) revealed similar results for FK506 and HA. [70] Zor et al investigated the effect of HA (film sheath at the site of neurorrhaphy), VEGF (VEGF gene in plasmid injection) and combined therapy, on axonal regeneration. The group subject to combined therapy had well myelinated, compact fibres aligned with SCs.…”
Section: Melatoninmentioning
confidence: 99%
“…We have conducted a review of 40 reports in which a rabbit animal model was used for evaluation of nerve regeneration. 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 To date, the sciatic nerve injury and repair model is the most well-documented nerve injury model in rabbits with 45% of studies performed using the sciatic nerve. In a study by Hsu et al, 19 a 2-cm section of the sciatic nerve was removed after making an incision from the greater trochanter to the mi-calf and splitting the muscle to expose the sciatic nerve.…”
Section: Introductionmentioning
confidence: 99%